Are Polish Kindergartens Ready for The Outdoors? The State of (Im)maturity of the Polish Educational System and its Selected Members for Outdoor Education - Łoboda, Hanna (Studia Ecologiae et Bioethicae, 2023)
As human beings, we are moving dramatically away from nature, which results in negative consequences for both mental and physical health. Highly developed countries see a special need to restore contact with nature as early as possible (Simonienko 2021, 74). Are Polish kindergartens also ready to provide children with education in nature? This article aims to describe the regulations of the educational law related to outdoor education in Polish kindergartens and to present the offer of educating teachers of early childhood education in the field of outdoor education at universities in Poland. Outdoor education is a term that does not have a clear equivalent in Polish. Depending on the translation and understanding, we can attribute different origins and meanings to it. The article presents terminological inaccuracies regarding outdoor education in Poland. The functioning of the education system is based on the activities performed by teachers, working both with the students and (indirectly) with parents. The last part of the text presents a description of selected attitudes of parents and children attending a forest kindergarten towards outdoor education.